2023
DOI: 10.1111/wre.12579
|View full text |Cite
|
Sign up to set email alerts
|

First report of glyphosate resistance in an Amaranthus palmeri population from Europe

Abstract: The invasive weed Amaranthus palmeri is spreading throughout Spain, with Catalonia being one of the most affected regions. For this species, acetolactate synthase‐inhibiting herbicide‐resistant populations have been reported, and now glyphosate resistance is also suspected. Glyphosate targets and inhibits the enzyme 5‐enolpyruvylshikimate‐3‐phosphate synthase (EPSPS), but A. palmeri has evolved different resistant mechanisms leading to plant survival. One of the most effective is the EPSPS overexpression due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…An organic fertilizer was used to test if its addition would result in higher availability and diversity of resources and alleviate competition compared to the non-fertilized treatment. A. palmeri has been introduced to Spain recently (Manicardi et al, 2023) but it is already expanding and becoming a management challenge.…”
Section: Introductionmentioning
confidence: 99%
“…An organic fertilizer was used to test if its addition would result in higher availability and diversity of resources and alleviate competition compared to the non-fertilized treatment. A. palmeri has been introduced to Spain recently (Manicardi et al, 2023) but it is already expanding and becoming a management challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides have been used to control weeds and increase the quality and quantity of major crops since their discovery. However, repeated use of similar herbicidal modes of action (MOAs) and the associated selection pressure have led to the evolution of herbicide resistance in varieties of economically important weedy species such as Alopecurus myosuroides ( Lan et al., 2022 ; Goldberg-Cavalleri et al., 2023 ), Amaranthus palmeri ( Manicardi et al., 2023 ), Apera spica venti ( Košnarová et al., 2021 ; Papapanagiotou et al., 2022 ), Bromus sterilis ( Sen et al., 2021 ), Lolium spp ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Zhu et al., 2023 ). Recent studies showed that the majority of these weeds were also developing multiple resistances against herbicides with more than one mode of action ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Košnarová et al., 2021 ; Lan et al., 2022 ; Papapanagiotou et al., 2022 ; Zhu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%